OPTIMALISASI EKSTRAKSI DAN UJI STABILITAS PHYCOCYANIN DARI MIKROALGA Spirulina platensis - Bakti Jos; Prayudi Eko Setyawan; Yudha Satria (TEKNIK, 2011)
The growing awareness of the importance of natural colours especially food and cosmetic colorants has placedgreat demand on biological sources of natural colours. It is for this reason that the phycobiliproteins inSpirulina platensis is gaining increasing attention as an alternative colour for these products. Numerousscientific reports confirm the fact that Phycocyanin from Spirulina platensis, is not only an effective naturalblue colorant, but also a compound that is beneficial to the health of the consumer. The aim of this research is toconduct evaluation studies phycocyanin production by extraction with polar solvents at various concentrationsto obtain extracts for maximum yield. The methods in this study has several stages, namely preparation ofmaterials, extraction, solubility studies of phycocyanin, phycocyanin’s stability test. Changing variables in thisstudy are water, acetic acid 70%, 75%, 80%, ammonium sulphate 50%, 55%, 60%. The analysis of the extractsof phycocyanin’s content using spectrophotometric methods. The observations produces a blue pigment whichhas the highest color intensity with maximum absorbance of 620 nm. Acetic acid 80% is the most effectivesolvent to extract the blue pigment phycocyanin than water and ammonium sulfate. Extraction is influenced bythe pH of the increase in absorption (absorbance) with increasing pH and was not influenced by storagetemperature and time